MINERALOGY AND GENESIS OF ULTRAMAFIC ROCKS FROM THE KURTUSHIBA OPHIOLITE BELT (WESTERN SAYAN) - V.A. Simonov; A.I. Chernyshov; A.V. Kotlyarov (Минералогия)
The studies of minerals and melt inclusions in ultramafic rocks of the Kurtushiba ophiolite belt (Western Sayan) allowed us to establish the conditions of mineral-forming processes during their formation. The features of the compositions of minerals of ultramafic rocks of the Idzhim, Kalny and Ergaki massifs are considered. The presence of melt inclusions directly indicates a magmatic origin of some Cr-spinels from dunites of the Idzhim massif. A close assemblage of Cr-spinels from chromitites with igneous Cr-spinels is important because of the possible formation of chromite ore from melts. The study of melt inclusions revealed the evolution of melts (picrites – picrobasalts – basalts – basaltic andesites) during the consecutive crystallization of minerals from the Western Sayan ophiolites. Computational modeling based on the compositions of melt inclusions and olivine indicates that olivine of ultramafic rocks of the Kurtushiba ophiolites crystallized at a decreasing pressure from 9.2 to 6.2 kbar and a decreasing temperature from 1550 to 1430 °С from picritic melts, which evolved to picrobasaltic melts. With a decrease in pressure to 3.8–2.3 kbar and temperature of picrobasaltic melts (1240–1230 °C), the formation of olivine terminated following by the crystallization of clinopyroxene from basaltic magmas at 2.7–1.9 kbar and about 1215 °C. The postmagmatic stage was characterized by plastic deformations of the Western Sayan ultramafic rocks at a decreasing temperature from 850 to 640 °C, which resulted in a successive change from protogranular to mesogranular structures and then to porphyroclastic and porphyroleist structures.